(untitled) (Perioperaciina Medicina, 2024)
Background. The problem of purulent inflammatory diseases of the maxillofacial area remains one of the most pressing problems of modern dentistry and maxillofacial surgery. The aim of the study is to conduct a comparative evaluation of the effectiveness of a drug based on nanodispersed silica (NDS) with antimicrobial properties for the local treatment of purulent inflammatory diseases of the maxillofacial area. Materials and methods. A comparative assessment of the postoperative period was performed in 71 patients with maxillofacial phlegmon, who were divided into two representative groups: comparison (39 patients), in whose local treatment of purulent wounds was carried out by conventional methods, and the main group (32 patients), where the local treatment was carried out using a drug based on NDC. The level of endogenous intoxication was determined by the level of C-reactive protein (CRP), by the level of blood metabolites of average mass (MAM) and leukocyte intoxication index (LII) in the blood serum. The data obtained were statistically processed and compared. Results. During the study of the dynamics of СRР was found that starting from 3 days in the main group there was a tendency to its faster decrease and normalization before discharge, while in patients of the comparison group it was significantly higher (p < 0.05)., The level of MAM in patients of the comparison group remained significantly (p < 0.05) elevated throughout the treatment in the postoperative period, while in the main group it was on the verge of normal before discharge. Comparison group of patients had significantly higher LII during treatment and at the time of discharge from hospital (p < 0.05) than the main group. Conclusions: The treatment of maxillofacial phlegmon by the developed method provided a more favorable course of the postoperative period than in the comparison group, as evidenced by a significantly (p < 0.05) faster normalization of endogenous intoxication blood parameters.